The “lean regional plan” — a new way forward? - Fürst, Dietrich; Peithmann, Ortwin (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
The authors point out the links between the proposed “lean regional plan” and various strands of the current discussion on reforming public administration. They place the regional plan within a dynamic context incorporating the contiguous instances of spatial and sectoral planning. From this they go on to derive three basic models of reciprocal displacement, which might provide a starting point for a more long-term overhaul of the German planning system. In the five proposals they put forward, the authors describe possible ways of reducing the content and procedures of regional planning in the shorter term without diminishing the degree of control afforded by the planning system.